Rice farming and the origins of cooperative behavior - Zhou, Xiaoyu; Alysandratos, Theodore; Naef, Michael (Social Science Research Network, 2021)
This paper provides novel evidence for links between historic farming practices and current norms of cooperation. We hypothesize that the cooperation required in wetland rice farming gives rise to strong cultural norms of cooperativeness. We compare participants from prefecture cities that predominately practice wetland rice cultivation, to those from non-rice regions. A public goods game with and without punishment is the main measure for cooperativeness. Results indicate a strong and robust positive effect of wetland rice farming on cooperation and pro-social punishment. Complementary, consistent evidence from a natural field experiment and a survey further enriches our data.
Gesehen am 11.02.2022